PERANAN INDUSTRI KECIL DALAM MENINGKATKAN PENDAPATAN MASYARAKAT Kasus Pada Industri Kerajinan Batik Kayu di Dusun Krebet, Sendangsari, Pajangan, Bantul - Josephine Wuri; Yuliana Rini Hardanti (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2006)
This research is intended to determine the most influencing variable towards the profit of craft men , and to identify the differences in profit based on production, marketing, and economic and social aspects. This research was conducted at the of batik kayu (batik motive painted on wood) industry located in Krebet, Pajangan, Bantul. Data employed in the study were primary data collected from the research location. The method of primary data collection was by questioner and direct interview to respondents. The Purposive Sampling Method was used in determining the samples, and the Multiple Linear Regression and Compare Means Test Method was used as the analysis method. The result of this research indicates that the value of production was the most significant variable that influenced the profit of craft men. Production aspect showed that there was a significant difference of profit means that based on the source of capital and the number of labor. Marketing aspect showed that there was not a significant difference of profit means on the craft men that do direct selling or selling through agent. There was not a significant difference of profit means between those who do and do not do advertising. Economic and social aspect showed that there was a significant difference of profit means based on craft men that have and do not have license.Keywords: Profit, Small and Medium Enterprise, Multiple Linear Regression, Compare Means Test.